Reconstruction of Total Lower Eyelid Defects with the Temporoparietal Fascial Flap - Simon R. Bababeygy; Anne R. Kao; Niels C. Kokot; Eli L. Chang (Case Reports in Ophthalmological Medicine, 2012)
Purpose. To describe the use of the temporoparietal fascial flap (TPF) in the reconstruction of extensive lower eyelid defects in a functioning eye. Methods. We present a surgical case report of a 73-year-old female with melanoma of the left lower eyelid. The lower eyelid was resected, and a composite nasal cartilage-mucosa graft, a skin graft, and a TPF were used to reconstruct the lower eyelid. Results. This achieved reconstruction of the lower eyelid with the protection of the eye and preservation of the visual system function. Conclusion. The TPF serves as a good option for reconstruction of the lower eyelid in a viable functioning globe.